Communication works - Gamble, Teri Kwal; Gamble, Michael , 1943- (New York : McGraw-Hill, 2013)
Presents a practical approach to communication, with a focus on the ways in which diversity, technology, social media, and ethical concerns both enrich and complicate our world. In this title, students learn what role communication plays in their lives today, in the classroom, and tomorrow, in the working world
1. Communication: begin right here! -- 2. Communicating in a multicultural society and world -- 3. The "I" behind the eye: perception and the self -- 4. Language and meaning: helping minds meet -- 5. Nonverbal communication: silent language speaks -- 6. Listening, Feedback, and critical thinking -- 7. Understanding relationships -- 8. Person-to-person: relationships in context -- 9. Groups and teams: strategies for decision making and problem solving -- 10. Leading others and resolving conflict -- 11. The speaker and the audience: the occasion and the subject -- 12. Researching, supporting, and outlining your speech -- 13. Preparing presentation aids and delivering your speech -- 14. Informative speaking -- 15. Persuasive speaking
Includes bibliographical references (p. 471-495) and index
Keywords: Communication